(untitled) (Annals of Medical Research, 2023)
Aim: In this study, it was aimed to evaluate the Turkish validity and reliability of the cardiac self-blame scale (CSBA) scale and to bring it to Turkish society. Materials and Methods: The research was methodological and descriptive. Data were obtained from 125 patients. Exploratory factor analysis (EFA) was used for the construct validity of the scale. The results showed that the scale can be used in Turkish society. The two-factor structure of the scale was preserved in this sample. Results: KMO value of the scale is 0,872. Bartlett Test values are x2=708,532 and p=0.001. The factor loads of the scale are between 0.444-1.13. In this study, the Cronbach’s alpha value of scale was 0.89. Conclusion: Findings obtained because of validity and reliability studies of cardiac self-blame attributions scale, which was adapted into Turkish, revealed can be used to determine the accusations against the behaviors and characters of individuals with cardiac disease in Turkish society.